Freud was not always scientific; so is psychology - deconstructing the present narratives - Paramboor, Jafar (2021)
This is an expansion of my talk delivered at an emerging institution of women empowerment, Zaitoon International Girls’ Campus of Kerala, India. They invited me as a speaker for the inaugural session of a psychology conference conducted in the middle of 2019 on the theme, rethinking the paradigm of psychology: scientific and religious perspectives. In this piece, I have attempted to clarify some of the points I made during the address, giving adequate references and notes wherever seemed apt.